ICES framework: Reconstruction of Islamic Character Education in Indonesia from a Global Sustainability Perspective - Suherman; Nasharudin bin Zainal; Syafril Barus (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to reconstruct Islamic character education from a global sustainability perspective by developing the ICES Framework as an integrative model. Theoretical Framework: This study is grounded in Islamic educational philosophy, character education theory, and the principles of education for sustainable development, which emphasize the integration of spiritual, ethical, social, and ecological dimensions in fostering responsible global citizens. Literature Review: Existing studies indicate character education in theoretical perspective, islamic character education from the perspective of islamic thought and education for sustainable development in theoretical perspective. Methods: This study employs a qualitative research approach based on library research. Data were collected from various scholarly sources, including journal articles, books, research reports, and relevant policy documents related to Islamic education, character education, and sustainability studies. The collected data were analyzed using thematic analysis and interpretative content analysis to identify, classify, and synthesize key concepts concerning Islamic values and global sustainability principles. Results: The findings reveal a strong epistemological convergence between Islamic values such as khalifah fil ardh, ‘adl, maslahah, amanah, and mizan and the core principles of global sustainability. Based on this convergence, the ICES Framework was developed, consisting of four interconnected dimensions: Islamic Values, Character Formation, Ethical Engagement, and Sustainability Orientation. The framework provides a comprehensive approach that integrates moral integrity, spiritual awareness, social responsibility, and ecological consciousness. Implications: The study underscores the importance of reorienting Islamic character education from a predominantly normative approach toward a reflective, contextual, and sustainability-oriented pedagogy. Such a transformation can contribute to the development of individuals who possess both strong moral character and a commitment to sustainable development. Novelty: The novelty of this study lies in the development of the ICES Framework, which systematically integrates Islamic character education with global sustainability principles, offering a conceptual model that bridges local religious values and contemporary global sustainability agendas, particularly in supporting the achievement of the Sustainable Development Goals.